BIOCONVERSION OF ALPHA-LINOLENIC ACID INTO LONG CHAIN POLYUNSATURATED FATTY ACIDS BY OLEAGINOUS FUNGI - DEVYANI SALUNKE,; RUPALI MANGALEKAR,; ANIKET KUVALEKAR,; ABHAY HARSULKAR, (International Journal of Pharma and Bio Sciences, 2014)
Long-chain polyunsaturated fatty acids (LCPUFA) i.e., eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have established role in the prevention of several diseases like atherosclerosis, cardiovascular disorders, and arthritis. However, LCPUFA sources are limited for availability and acceptability problems of fish and flax oil. Microbial sources of n-3 PUFA are of merit being cheaper, contamination free and vegan. We here report fungi that can convert ∝-linolenic acid (ALA) from flax seed meal (FSM) into EPA and DHA in dose-dependent manner and therefore serve as valuable LCPUFA sources. Mucor sp. and R. oligosporous cultivated on FSM supplemented medium accumulated 34 and 36% lipids of dry biomass. Wherein, Mucor sp produced 6.01mg DHA per gram of lipid at 10% FSM at 28°C, while Rhizopus oligosporus produced 14.32 mg of DHA/gm of lipid at 3% FSM at 20°C. These novel yet exploitable sources of LCPUFA are valuable to ensure EPA/DHA for human supplementation.